Sir John Edward Sulston CH. 27 March 1942—6 March 2018. (12th December 2019) - Waterston, Robert H.; Ferry, Georgina
Abstract : In 2002 Sir John Sulston shared the Nobel Prize for Physiology or Medicine for his contribution to understanding the genetic control of cell fate during the development of the roundworm Caenorhabditis elegans . However, it was his position as one of the leaders of the international and publicly funded Human Genome Project that brought him to public prominence. Both his work on the worm cell lineage and his later commitment to genome sequencing as founding director of the Wellcome Trust Sanger Institute stemmed from his conviction that investing in large-scale data collection would have long-term benefits for future scientific discovery. He was a key figure in promoting the principle, now widely accepted, that genomic data should be universally and freely shared. After retiring from his post at the Sanger Institute he engaged with organizations with interests in biomedical ethics and global equality. He was a loyal and supportive colleague to many, delighting in the international collegiality of the 'worm community', of which he was a founding member.